Role of Platelet-Rich Plasma in Patients with Adhesive Capsulitis Shoulder - Shah, Sayed Moinuddin; Peracha, Muhammad Asif; Shah, Rukan Aalamuddin; Siyal, Shahjahan; Ahmed, Nasir; Ali, Rehan Ramzan; Shaikh, Abdul Mueed; Hassan, Humayun; Ahmed, Syed Ahsanuddin (Indus Journal of Bioscience Research, 2025)
Background: Reduced shoulder joint range of motion and persistent discomfort are symptoms of adhesive capsulitis. Patients with a range of orthopaedic conditions may benefit from platelet rich plasma (PRP) injections in terms of pain management and functional results. Objective: To determine the efficacy of platelet-rich plasma in patients with adhesive capsulitis shoulder visiting Liaquat National Hospital Karachi. Material and Methods: A descriptive cross-sectional study was conducted on 169 patients of either gender with age 30–60 years. Patients received four weekly PRP injections guided anatomically, with standardized post-procedure shoulder exercises. Pain severity was assessed using the Visual Analogue Scale, and ≥50% reduction at six weeks was considered effective. Data were analyzed using SPSS. Chi-square/Fisher’s Exact tests were applied considering p ≤ 0.05 as significant. Results: Total 73.4% were males and 26.6% were females. Means age was 48.01±8.96 years. Patients had symptoms for an average of 15.5 weeks, and PRP therapy led to notable pain reduction from a mean score of 8.86 to 4.38 after six months. Treatment was effective in 53.3% cases, while 46.7% saw limited improvement. No demographic, clinical, or lifestyle factors including gender, age, BMI, residence, comorbidities, smoking status, or symptom duration showed statistically significant associations with treatment efficacy (p >0.05). Logistic regression echoed these findings, with no variable emerging as a significant predictor. Conclusion: When platelet-rich plasma was injected intra-articularly into Adhesive Capsulitis-affected shoulders, the pain intensity decreased and the capacity to do everyday tasks improved.